Description and conservation status of a new species of Australotomurus (Collembola: Entomobryidae: Orchesellinae) from urban Perth remnant bushland - Greenslade, Penelope; Jordana, Rafael (Zootaxa, 2014)
A new species of the Australian endemic genus Australotomurus Stach, 1947 A. morbidus sp. nov., is described from four urban remnants in Perth. Australotomurus morbidus sp. nov. is the first species in the genus found to possess male secondary sexual characters on antennal segment III as well as I. The males of all other described species in the genus occurring in south-eastern Australia have secondary sexual characters on antennal segments I and II rather than I and III. Typical habitats for Australotomurus species are long undisturbed native grasslands and heathland at low and high elevations. The new species extends the known distribution of the genus ca. 2,000 km west. Australotomurus morbidus sp. nov. is the only species in the genus currently vulnerable to extinction because of its restricted distribution to only four localities, all of which are subject to considerable human disturbance. This species was listed as critically endangered when it was known (but not yet described) from only one locality but was delisted a few years later when three other locations for the species were found. The history and records of A. morbidus sp. nov. suggest that listing species using current Western Australian legislation does not necessarily protect vulnerable species. The new species is described here and new records for some other Australian species of Orchesellinae provided, including the first Australian record of Heteromurus major (Moniez, 1889).